Q: Factor m2 plus 6n - 9n2 - 2m?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(m - 3n)(m + 3n - 2)

12m + 9n - 4 - 10m + 6n = 2m + 15n - 4

factor by grouping 7m(m-2)+6n(2-m)

3(3n - 1)(n + 1)

n^2(n + 6)(n^2 - 6n + 36)

Related questions

m^2 6n - 9n2 - 2m = (m - 3n)(m + 3n - 2)

(m - 3n)(m + 3n - 2)

11m + 6n - 2m + 9n = 9m + 15n or 3(3m + 5n)

12m + 9n - 4 - 10m + 6n = 2m + 15n - 4

-2m^4n(8m^3 - 6n^7 - 9)

7n3 + 6n = n*(7n2 + 6)

The GCF is 6.

factor by grouping 7m(m-2)+6n(2-m)

3(3n - 1)(n + 1)

6n2 + 16n can be factorised to give 2n(3n + 8) so the highest factor is 2n.

6n + 5n is 11n.

2(n2+3n-54) 2(n+9)(n-6)